1998
DOI: 10.1002/biof.5520070104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF‐κB transcriptional activity by α‐tocopheryl succinate

Abstract: The role of vitamin E in cell regulation in addition to its function as an antioxidant has attracted attention. The effects of alpha-tocopherol (T) and alpha-tocopheryl succinate (TS) on transcriptional activation of the tumor necrosis factor alpha (TNF-alpha) gene and nuclear factor kappa B (NF-kappa B) activation were examined. Two stable transformants were used: TR-1 cells derived from THP-1 cells transfected with a vector contains the human TNF-alpha promoter (1.4-kb) joined to the human placental alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…In addition, 2 antioxidant compounds present in red wine, quercetin and ␣-tocopherol succinate, inhibited this activation, and ethanol did not modify NF-B activation induced by VLDL (not shown). In this sense, ␣-tocopherol succinate, a vitamin E derivative, inhibits NF-B activation in Thp-1 cells induced by lipopolysaccharide, 38 and quercetin inhibits interleukin-8 and monocyte chemoattractant protein-1 expression in synoviocytes. 39 However, Wadsworth et al 40 reported that quercetin and resveratrol did not inhibit lipopolysaccharide-induced activation of NF-B in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 antioxidant compounds present in red wine, quercetin and ␣-tocopherol succinate, inhibited this activation, and ethanol did not modify NF-B activation induced by VLDL (not shown). In this sense, ␣-tocopherol succinate, a vitamin E derivative, inhibits NF-B activation in Thp-1 cells induced by lipopolysaccharide, 38 and quercetin inhibits interleukin-8 and monocyte chemoattractant protein-1 expression in synoviocytes. 39 However, Wadsworth et al 40 reported that quercetin and resveratrol did not inhibit lipopolysaccharide-induced activation of NF-B in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are known to be potent activators of the nuclear transcriptional factor, NF-ÎB [4], while the addition of antioxidants such as vitamin E or the overexpression of antioxidant enzymes such as glutathione peroxidase can block activation of the transcriptional factor [5,6]. In addition, increased NF-ÎB expression has been linked to ROS-induced cell death [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some constituents are free radical scavengers (Cos et al, 1998) and are therefore able to reduce tissue damage caused by oxidation stress of superoxide, hydroxyl and lipid peroxidation products. Green tea polyphenols, curcumin, and resveratrol inhibit the activation of NF B and also have antioxidant activity (Nakamura et al, 1998;Shishodia et al, 2003). They are considered as moderate antiinflammatory agents and could be used for preventive therapy and perhaps as therapeutics for the treatment of inflammation related diseases (Yamamoto and Gaynor, 2001).…”
Section: General Inhibitory Pathways Of Inflammation By Phytomedicinamentioning
confidence: 99%